Ludvig Holberg og fejden med Johann Arckenholtz - Schmidt, Kristoffer (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
Kristoffer Schmidt: Ludvig Holberg and his feud with Johann Arckenholtz In 1751, the Swedish librarian Johann Arckenholtz published the first two volumes of his work Memoires Concernant Christine Reine de Suede. The work was mainly a panegyric defence of Queen Christina of Sweden who abdicated in 1654. Christina was a controversial figure in her own time and both contemporary and later authors criticised some of her more dubious actions. Being a fan of the Swedish queen, Arckenholtz defended his heroine vigorously and accused many of her critics of writing untruthful character assassinations. One of these critics was the Danish historian and playwright Ludvig Holberg. Holberg objected to the criticism by writing a rebuttal where he not only rejected Arckenholtz’ views but also accused him of being more of a panegyrist than an actual historian. This sparked a heated debate between the two authors, which would receive international attention. Despite the contemporary interest historical studies about the debate are scarce and inadequate. The purpose of this article is threefold: 1) It gives a detailed account of the feud between Holberg and Arckenholtz; 2) It examines why the feud between the authors became so heated; 3) It examines the Danish-Norwegian, Swedish and international reception of the dispute.